Pedagogical Reflection as a Determinant of the Development of Professional Competence and Pedagogical Mastery of Future Socionomic Profile Specialists in the Structure of Foreign Language Training - Telichko, Natalia (Pedagogical Discourse, 2025)
The article is aimed to identify the urgent problem of the need to improve the quality of foreign language training for future socio-economic specialists by developing pedagogical reflection, which is a determining factor in the formation of their professional competence and pedagogical skills. The purpose of the study is to reveal the current problems of improving the quality of foreign language training of future socio-economic specialists through the development of pedagogical reflection, which becomes a determining factor in the formation of their professional competence and pedagogical skills. The essence of pedagogical reflection in the context of professional training for future socio-economic specialists has been revealed; its functions and possibilities of influencing the quality of mastering foreign language knowledge, skills and professionally oriented communicative skills have been analyzed. The psychological and pedagogical features of future socio-economic specialists, their readiness for reflective activity, as well as the specifics of organizing foreign language training in higher education have been analyzed. It is substantiated that the systematic involvement of students in reflective practices contributes to the development of their professional self-awareness, the ability to analyze their own educational activities, determine individual strategies for foreign language development and build effective trajectories of professional development. It is emphasized that the quality of foreign language training largely depends on the ability of students to reflect on their own communicative actions, assess the level of formation of foreign language skills, identify difficulties and adjust ways to overcome them. It is substantiated that a teacher should have a developed reflective culture, the ability to design learning situations that stimulate the conscious use of a foreign language, the formation of critical thinking, self-analysis and professional self-improvement of students.